Understanding America's Industries / Second Edition - Gerbracht Carl; Robinson Frank E (Mcknight And Mcknight Publishing Company, 1971)
Industrial Arts, Wood Industries, Metal Industries, Graphic Art Industries, Ceramic and Related Industries, Electrical Industries, Textile Industries, Mass Production, Mining and Fuels and Power, From Producer to Consumer, Index.